Artificial Intelligence for Knowledge Management Third IFIP WG 12.6 International Workshop, AI4KM 2015, Held at IJCAI 2015, Buenos Aires, Argentina, July 25-31, 2015, Revised Selected Papers - Mercier-Laurent, Eunika; Boulanger, Danielle (IFIP Advances in Information and Communication Technology,, 2016)
This book features a selection of papers presented at the Third IFIP WG 12.6 International Workshop on Artificial Intelligence for Knowledge Management, AI4KM 2015, held in Buenos Aires, Argentina, in July 2015, in the framework of the International Joint Conference on Artificial Intelligence, IJCAI 2015. The 9 revised and extended papers were carefully reviewed and selected from 15 submissions. They present new research and innovative aspects in the field of knowledge management such as knowledge models, KM and Web, knowledge capturing and learning, and KM and AI intersections.